An intervention to develop English reading abilities of second language grade 9 learners - Long, Susanne Ingeborg (My University, 2008)
In support of educational equity, the White Paper 6 (Department of Education, 2001) states that every learner in South Africa has the right to pursue their learning potential to the best of their ability. The South African Schools Act of 1996 states that a school’s language policy may not exclude learners from different backgrounds. As a result, many English second language (L2) learners struggle to understand the learning material and perform poorly academically. Poor literacy and reading skills have been identified in the literature (for example Pretorius, 2005) as a significant cause for poor academic performance. In an endeavour to work within the Outcomes Based Education (OBE) system, teachers are increasingly seeking ways to improve group learning. These factors motivated the present study and a paired reading intervention was selected and administered to Grade 9 English second language learners. Volunteer participants consisted of an Experimental Group (n 53) and a Comparison Group (n 53). Each group was divided into strong (mentor) and weak (mentee) readers. Pre-tests and post-tests were conducted regarding the Experimental and Comparison Group’s scores on the Vocabulary and Comprehension subtests of the Stanford Reading Diagnostic Test (SDRT): Brown Level and the Academic Performance of both groups were recorded at pre and post-test phases. After an 11 week intervention programme a statistical analysis of the results was conducted. The overall means for the groups were analysed using t-tests to establish any significant differences between the pre-test and post-test results. An Analysis of Covariance (ANCOVA) was also conducted to determine whether any significant differences existed between the Experimental and Comparison Group. A null hypothesis was supported. It would appear that the whole-hearted commitment and participation of all role-players is essential for the effective implementation of a peer reading intervention at a school.
Keywords: Reading; Comprehension; Vocabulary; Paired Reading Intervention; English Second Language Learner (L2); English First Language Learner (L1).